Penguatan Hubungan antar-Institusi dalam Pengembangan Pendidikan Islam: Implementasi MoU antara IAI Almuslim Aceh dan Maahad Tahfiz Kiblah Malaysia - Diana, Diana; Shapawi, Ahmad Muzammil Mohamed; Muksalmina, T.; Sunnisak, Ria (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2023)
This community service-based research aims to evaluate and develop the implementation of the Memorandum of Understanding (MoU) between IAI Almuslim Aceh and Maahad Tahfiz Kiblah. The study adopts a collaborative and participatory Action Research approach, involving faculty members, students, and stakeholders from both institutions to work together in enhancing the quality of Islamic education and the capacity of educators. The research method involves stages of planning, action, observation, and reflection. The planning stage includes identifying the needs and issues at IAI Almuslim Aceh, followed by the implementation of programs such as On-the-Job Training (OJT), faculty training, and the development of a joint curriculum that integrates Islamic educational values and Acehnese local wisdom. The results of the study indicate that the OJT program and faculty training have had a significant positive impact on the development of competencies among students and lecturers, as well as on the enhancement of teaching skills that are technology-based and interactive. The development of the joint curriculum has also successfully created a more holistic learning approach, integrating cognitive, affective, and psychomotor aspects, and aligning with both global challenges and local needs. The implications of this research include the development of an effective inter-institutional collaboration model to improve the quality of Islamic education, strengthen educator capacity, and promote inclusivity and sustainability in community service-based educational programs.